PERAN MUSIK GEREJAWI DALAM PEMBENTUKAN IMAN JEMAAT DI ERA DIGITAL - Gunawan Tonapa; Marson Toding, Altini, Nimrod Sarira, Kris Verajanti (ADISAM PUBLISHER, 2025)
Church music has, from the beginning, been a vital element in the life of Christians not merely as a complement to worship, but as a means of praise, worship, teaching, and the strengthening of faith. In the digital era, music has undergone a transformation in its production and distribution through various online platforms such as YouTube, Spotify, and social media, enabling congregants to access spiritual songs anytime and anywhere. This transformation presents a significant opportunity for faith formation but also brings risks, such as decreased active participation, a shift in the meaning of worship, and the consumption of theologically shallow content. This paper discusses the role of church music in shaping the faith of believers in the digital era by highlighting the dynamics, challenges, and potential brought about by technological developments. Through an analysis of the functions of music in worship, an understanding of Christian faith, and the church's adaptation in the digital age, this study emphasizes that church music still holds great potential as a tool for spiritual formation when properly directed. Grounded in the Word of God and supported by a contextual approach, music can continue to be a living medium to build, strengthen, and deepen the faith of the congregation, even in a world increasingly connected through digital means